Some Issues in the Strategic University Management - Nurul Nazihah, Hawari; Razman, Mat Tahar (2011)
Universiti Utara Malaysia (UUM)has been described as the first Malaysian university with a broad Management scope. Today, in the quest to be among notable universities in the nation and world, UUM is striving hard to be a comprehensive research university that blends the main elements of national agenda, education missions and sustainable research tradition. One of the core strategies is to develop a culture of excellence in scholarly activities. This paper describes how system thinking can help in developing a shared vision within the University for achieving the ambition.